2022
DOI: 10.3390/economies10020048
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights in the Leadership in Business and Economics: A Post-Coronavirus Update

Abstract: Our world is evolving at an incredibly enormous speed and what was impossible three years ago is now a reality. The concept of leadership and leaders has also undergone profound transformations. Moreover, the recent COVID-19 pandemic caused a digital surge in the ways economic life, business, or education are perceived or conducted. The pandemic proved that small and large businesses, industries, and the whole economies can be suddenly upended by massive technological shifts. Hence, there is a need for a theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 123 publications
2
10
0
1
Order By: Relevance
“…It can be proclaimed that COVID-19 pandemic has created previously unknown situations and new models of interactions within our society. The crisis has shown that restrictive measures are not beneficial for the economy and are popular with the general public (Arias-Maldonado, 2020;Faggioni et al, 2021;Strielkowski et al, 2022). All of these caused extensive damage and numerous issues, especially of an economic nature, inter alia in tourism, and specifically in the hospitality sector (Khalid et al, 2021;Ozbay et al, 2021;Peco-Torres et al, 2021;Kennedy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It can be proclaimed that COVID-19 pandemic has created previously unknown situations and new models of interactions within our society. The crisis has shown that restrictive measures are not beneficial for the economy and are popular with the general public (Arias-Maldonado, 2020;Faggioni et al, 2021;Strielkowski et al, 2022). All of these caused extensive damage and numerous issues, especially of an economic nature, inter alia in tourism, and specifically in the hospitality sector (Khalid et al, 2021;Ozbay et al, 2021;Peco-Torres et al, 2021;Kennedy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity analysis was carried out in terms of net present value (NPV) in the range from -20% to + 20% of the change in the studied indicators. This interval is considered sufficient to draw conclusions about the stability of the investment project [57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Resultsmentioning
confidence: 99%
“…Os artigos que deram ênfase aos processos de gerenciamento e estratégias de TD apontaram conceitos como eficiência, eficácia, resiliência organizacional e valor compartilhado. A partir dos conceitos de liderança sustentável e resiliência organizacional, Strielkowski et al (2022) indicam que essa nova onda de tecnologia e inovação, fortemente acelerada pela pandemia, 8 oferece às empresas a oportunidade não apenas de fazer mudanças radicais com impacto na produtividade e eficiência, mas também de capturar valores estratégicos de negócios, alcançando patamares elevados de vantagem competitiva a partir do gerenciamento da cadeia de valor.…”
Section: Gerenciamento E Transformação Digitalunclassified